Labor Statistics Measurement Issues. - Haltiwanger, John (Studies in income and wealth., 1998)
Rapidly changing technology, the globalization of markets, and the declining role of unions are just some of the factors that have led to dramatic changes in working conditions in the United States. Little attention has been paid to the difficult measurement problems underlying analysis of the labor market. Labor Statistics Measurement Issues helps to fill this gap by exploring key theoretical and practical issues in the measurement of employment, wages, and workplace practices. Some of the chapters in this volume explore the conceptual issues of what is needed, what is known, or what can be l.